Pest categorisation of Gilpinia hercyniae. (14th December 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; Niere, Björn; et al.
Abstract: The Panel on Plant Health performed a pest categorisation of the Diprionid sawfly, Gilpinia hercyniae Hartig (Hymenoptera: Diprionidae), for the EU. G. hercyniae is a well‐defined and distinguishable species, native to Europe but also present in North America, Japan, Mongolia, Korea and Pakistan, and recognised as a pest of spruce ( Picea spp.). The pest is distributed in 19 Member States (MSs) of the EU. It is a quarantine pest listed in Annex IIB of Council Directive 2000/29/EC. Protected zones are in place in Greece, Ireland and the United Kingdom (Northern Ireland, Isle of Man and Jersey). Plants for planting of Picea spp. and soil and litter associated with Picea spp. are considered as pathways for this pest, which is also able to disperse by flight. The prepupae overwinter inside cocoons in the litter or in the foliage. In spring, the adults, mostly females emerge and lay 35–60 eggs per female in mature needles. The larvae feed on the mature needles through five instars. There are 1–3 generations per year; some of the prepupae undergo prolonged diapause for more than 1 year. The impact on Picea abies (= excelsa ) is minimal, because only the needles of the previous years are attacked; however, outbreaks have occurred on non‐native spruce, Picea glauca and Picea sitchensis . The pest is controlled everywhere by natural enemies, including nuclear polyedrosis viruses. The insects spread on plants for planting of Picea spp., with soil and litter associated with Picea spp., and by flight. The EU protected zones have a similar climate and similar host plants as the MS where G. hercyniae is established. All criteria assessed by EFSA for consideration as potential protected zone quarantine pest and as a potential regulated non‐quarantine pest were met.